Disconnect to reconnect: The food/technology metaphor in digital detoxing - Sutton, T (University of Illinois at Chicago Library, 2017)
The idea of "going on a digital detox" arrives as a response to a proliferation of digital technology and a concern that this addictive form of sociality erodes meaningful or authentic connection. This paper explores concerns about our relationship with digital technology through a short ethnography of Camp Grounded: a Californian digital detox retreat and summer camp for adults. At Camp Grounded, digital detoxers conceptualise consumption of technology using a food parallel. While the brief connection or "snack" of a text message might temporarily satisfy, detoxers feel that waiting for a more nutritious face-to-face encounter will ultimately be more emotionally nourishing. This paper interrogates the food/technology metaphor to unpack its analytical limitations and the questions it prompts about the future of our relationship with digital technology.